Integrating Artificial Intelligence into Islamic Religious Education: Toward a Model for Ethical and Values-Based Technology Adoption in Faith-Based Schools - Yadi Fahmi Arifudin; Akil Akil (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
This study investigates the perceptions, challenges, and opportunities of integrating Artificial Intelligence (AI) into Islamic Religious Education (PAI) at SMA IT Mentari Ilmu Karawang, a faith-based secondary school. While grounded in this specific institutional context, the findings are framed to provide transferable insights for similar Islamic-oriented institutions, serving as both a localized case and a reference for broader models of ethical and values-based AI adoption. Using a descriptive qualitative approach, data were collected through semi-structured interviews with PAI teachers, the vice principal, and the school principal. The results indicate that AI is appreciated for supporting personalized, inclusive, and efficient learning, yet it cannot replace the teacher’s role in moral and spiritual formation. Challenges include ethical concerns, limited infrastructure, and the absence of Islamic contextualized regulations, while opportunities involve curriculum innovation, workload reduction, and adaptive instruction. Theoretically, this study advances the conceptualization of AI in values-based education within the discourse of Islamic Religious Education. Practically, it proposes a transferable framework for ethical and transformative AI adoption, guiding schools, teachers, and policymakers to align technology use with Islamic ethical principles. Future research directions include developing an Islamic AI curriculum, piloting an integrative AI Adab model, and conducting comparative studies across faith-based institutions to identify scalable best practices.Keywords: Artificial Intelligence, Islamic Religious Education, Teacher Perception, Educational Technology, Ethics